Analysis of the Management of Early Childhood Education Institutions Using the ADDIE Model at KB Aisyiyah Kutukulon Ponorogo - Feby Eka Listiani; Navima; Rengga Aprilia; Putri Maulidatul Hasanah; Ahmad Fajarusshidiq (Universitas Negeri Surabaya, 2025)
This study aims to describe the management condition of the PAUD institution and analyze the direction of service development at KB Aisyiyah Kutukulon Ponorogo using the ADDIE Model (Analysis, Design, Development, Implementation, Evaluation) approach. The research was conducted through observation, in-depth interviews, and document analysis to obtain a comprehensive picture of the division of teacher duties, learning implementation, classroom management, parental involvement, and learning infrastructure facilities. The results of the study show that institutions face a number of obstacles, such as multi-role teachers with high administrative burdens, limited classrooms and educational game tools, the absence of contingency plans when teachers are unable to attend, and parental involvement which is still informative. Through the ADDIE model, the needs of the institution were successfully mapped systematically: the Analysis stage revealed the main managerial problems; the Design stage to design improvement strategies related to task division, strengthening classroom management, structuring facilities, and parent collaboration programs; Development stage produces SOPs, training modules, classroom layouts, and child development assessment instruments; The Implementation stage describes the scheme of implementing the solution; while the Evaluation stage emphasizes the importance of continuous evaluation to improve service quality. This study concludes that the ADDIE Model can be an effective strategic framework to develop the quality of PAUD management, especially in institutions with limited resources.